YouTube and Music Online Culture and Everyday Life - Rogers, Holly; Freitas, Joana; Porfírio, João Francisco (New Approaches to Sound, Music, and Media, 2023)
YouTube has afforded new ways of documenting, performing and circulating musical creativity. This first open access sustained exploration of YouTube and music shows how record companies, musicians and amateur users have embraced YouTube's potential to promote artists, stage performances, build artistic (cyber)identity, initiate interactive composition, refresh music pedagogy, perform fandom, influence musical tourism and soundtrack our everyday lives. Speaking from a variety of perspectives, musicologists, film scholars, philosophers, new media theorists, cultural geographers and psychologists use case studies to situate YouTube as a vital component of contemporary musical culture. This book works together with its companion text Remediating Sound: Repeatable Culture, YouTube and Music. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.